ANALISIS RELIABILITY DAN UMUR PAKAI BEARING 6207 DENGAN MENGGUNAKAN METODE WEIBULL - Dwilestari, Charisma; Feriyanto, Dafit (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Bearing is a mechanical component that is used as a place where the shaft rests on its axis and rotates with the holder and the shaft. The use of these bearings is focused on reducing friction; therefore, the friction that occurs is getting bigger along with the load, pedestal, working temperature, and conditions of loading and rotation that occur on the shaft. Estimation of damage and bearing life will be carried out on several bearings from different brands, but with the same type and size. Bearings with type 6207 and bore diameter of 35 mm come from 7 brands, namely SKF-SS (the only type in this study that used stainless steel), SKF, NSK, NACHI, KOYO SEIKO, SKF, and NTN. This analysis is carried out using the Weibull method where bearing specification data is processed by entering data into existing equations and analyzing the results of the calculations performed. The dynamic load value affects the L10 value of 9.3217%, predicted R(t) 13.5349%, ηcat 9.2567%, and Actual Reliability 3.9158%, this is due to the relationship between each of the equations used. Based on the reliability value generated, it can be concluded that the type of bearing recommended is NTN.